(untitled) (IDENTITĂȚI COLECTIVE ȘI IDENTITATE NAȚIONALĂ. PERCEPȚII ASUPRA IDENTITĂȚII ÎN LUMEA MEDIEVALĂ ȘI MODERNĂ. ln memoriam Alexandru Duţu, 2026)
The analyses and studies presented in this volume offer, on the one hand, historical perspectives—images spanning time and space—regarding the issue of identity; on the other, they reflect the unique vision of a group of young historians concerning concrete approaches to this field. This research prioritizes the realm of the concrete—of the historical phenomenon in its evolution—in an effort to demonstrate analytical possibilities and open up numerous avenues for future inquiry. Furthermore, these works were written with the firm conviction that nothing is immutable and, above all, that every new "brick" added to the historiographical edifice—even one that is fragile or imperfectly finished—can serve as the starting point for future debate. The scope of analysis is diverse, mirroring the breadth of the time and space covered by the research.